2004
DOI: 10.1136/hrt.2003.017137
|View full text |Cite
|
Sign up to set email alerts
|

The role of echocardiography in diagnosing double chambered right ventricle in adults

Abstract: Patients: 32 patients, mean age 32.5 years, 21 female, and 11 male. Intervention: Transthoracic (TTE) and transoesophageal (TOE) echocardiographic examination in patients with suspected DCRV. Main outcome measures: Direct inspection during surgical treatment of 28 patients diagnosed as having DCRV as an isolated lesion or associated with other pathologies. Results: Echocardiography allowed the final diagnosis of DCRV in 26 patients (81%) out of 32 studied. TTE was diagnostic in 5 (15.6%) whereas TOE was diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
127
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 9 publications
(1 reference statement)
2
127
0
10
Order By: Relevance
“…Daha önceki çalışmalar transtorasik ekokardiyografi ile erişkinlerdeki çift odacıklı sağ ventrikül olgularının yalnızca %8-17 oranında doğru tanı koyulabileceğini göstermiştir [6,14,15]. Bu olgularda transezofageal ekokardiografi ve kalp kateterizasyonu yapılması tavsiye edilmektedir.…”
Section: Discussionunclassified
“…Daha önceki çalışmalar transtorasik ekokardiyografi ile erişkinlerdeki çift odacıklı sağ ventrikül olgularının yalnızca %8-17 oranında doğru tanı koyulabileceğini göstermiştir [6,14,15]. Bu olgularda transezofageal ekokardiografi ve kalp kateterizasyonu yapılması tavsiye edilmektedir.…”
Section: Discussionunclassified
“…During the 4 th to 7 th weeks, the heart undergoes into a typical four-chambered structure with endocardial cushions, which have critical role in many cardiac deformities (5). DCRV is relatively rare as an isolated anomaly (approximately 0.5-2% of CHD) with no inheritance pattern (6). Patients with DCRV frequently have other congenital cardiac anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac magnetic resonance imaging and invasive testing can provide further information to confirm the diagnosis and guide therapeutic decisions [5]. Many authors have reported a high incidence of concomitant congenital disease; up to 90% of cases are associated specifically with membranous-type ventricular septal defects [6].…”
Section: Discussionmentioning
confidence: 99%
“…The most effective form of diagnosis of DCRV is TEE [6]. Use of continuous Doppler also allows for the calculation of intraventricular pressure gradients and obviates the need for additional cardiac catheterization [6,7]. On echocardiography, fibrotic and hypertrophic tissue is more evident during systole, since the muscle bands are contracted and thickened [8].…”
Section: Discussionmentioning
confidence: 99%